Transformation of human CD34+ hematopoietic progenitor cells with DEK-NUP214 induces AML in an immunocompromized mouse model - Qin, Haiyan (Oncogene, 2016)
AML is a heterogeneous disease comprising a large number of subtypes defined by specific chromosome abnormalities. One such subtype carries the t(6;9)(p22;q34) chromosome rearrangement which leads to expression of the DEK-NUP214 chimeric gene, and has a particularly poor outcome. To provide a better understanding of the molecular etiology of these relatively rare individual AML variants, it is necessary to generate in vivo models, which can also serve as a means to evaluate targeted therapies based on their specific genetic abnormalities. Here we describe the development of a human cell AML, generated in CD34+ human hematopoietic progenitor cells xenografted into immuncompromised mice that express human myeloid cell growth factors. Within six months, these mice develop a human cell AML with phenotypic characteristics of the primary t(6;9) disease and a CD45+CD13+CD34+CD38+ immunophenotype. Gene expression studies show that members of the HOX family of genes (HOXA9, 10, B3, B4 and PBX3) are highly upregulated in the AML from this mouse model as well as from primary human t(6;9) AML. Gene expression analysis also identified several other significantly disregulated pathways involving KRAS, BRCA1 and ALK, for example. This is the first report of a humanized model of the DEK-NUP214 disease and provides a means to study the development and treatment of this particular subtype of AML.